Effects of an Antihypertensive Combination Based on the Long-Acting Calcium Channel Blocker Benidipineon Vascular and Renal Events: a Sub-Analysis of the COPE Trial. (June 2015) - Umemoto, Seiji; Ogihara, Toshio; Matsuzaki, Masunoti; Rakugi, Hiromi; Shimada, Kazuyuki; Ohashi, Yasuo; Hayashi, Koichi; Makino, Hiroshi; Saruta, Takao
Abstract : Background: The Combination Therapy of Hypertension to Prevent Cardiovascular Events (COPE) trial compared three regimens based on the calcium channel blocker (CCB) benidipine.Hypertensive outpatients between the ages of 40–85 years who did not achieve the target blood pressure (<140/90 mmHg) with 4 mg/day of benidipine received an additional angiotensin receptor blocker (ARB), β-blocker, or thiazide. The analysis included 3, 293 patients who received an ARB ( n = 1, 110), β-blocker ( n = 1, 089), or thiazide ( n = 1, 094) in addition to benidipine and were followed for a median of 3.61 years. The COPE trial demonstrated a significantly higher incidence of hard cardiovascular composite endpoints and of fatal or non-fatal strokes in the benidipine-β-blocker group than in the benidipine-thiazide group ( P = 0.0201, P = 0.0109, respectively). Objective and Methods: In this pre-specified sub-analysis, we further evaluated treatment effects of the three benidipine-based regimens on vascular and renal events. Results: We observed a total of 10 vascular events(0.8 per 1, 000 person-years) including 9 cases ofperipheral artery disease (0.8 per 1, 000 person-years) and 1 aortic dissection (0.1 per 1, 000 person-years). We also observed a total of 7 renal events (0.6 per 1, 000 person-years).Few differences were observed among the three treatment groups regarding vascular and renal events (vascular events, P = 0.29; renal events, P = 0.16, Log-rank test). Conclusions: This sub-analysis of the COPE trial demonstrated that blood pressure-lowering therapy with benidipine combined with an ARB, β-blocker, or thiazide diuretic was similarly effective in the prevention of vascular and renal events in hypertensive outpatients.